Immune checkpoint CD47 molecule engineered islets mitigate instant blood‐mediated inflammatory reaction and show improved engraftment following intraportal transplantation. Issue 10 (27th May 2020) - Shrestha, Pradeep; Batra, Lalit; Tariq Malik, Mohammad; Tan, Min; Yolcu, Esma S.; Shirwan, Haval
Abstract : Instant blood‐mediated inflammatory reaction (IBMIR) causes significant destruction of islets transplanted intraportally. Myeloid cells are a major culprit of IBMIR. Given the critical role of CD47 as a negative checkpoint for myeloid cells, we hypothesized that the presence of CD47 on islets will minimize graft loss by mitigating IBMIR. We herein report the generation of a chimeric construct, SA‐CD47, encompassing the extracellular domain of CD47 modified to include core streptavidin (SA). SA‐CD47 protein was expressed in insect cells and efficiently displayed on biotin‐modified mouse islet surface without a negative impact on their viability and function. Rat cells engineered with SA‐CD47 were refractory to phagocytosis by mouse macrophages. SA‐CD47‐engineered islets showed intact structure and minimal infiltration by CD11b + granulocytes/macrophages as compared with SA‐engineered controls in an in vitro loop assay mitigating IBMIR. In a syngeneic marginal mass model of intraportal transplantation, SA‐CD47‐engineered islets showed better engraftment and function as compared with the SA‐control group (87.5% vs 14.3%). Engraftment was associated with low levels of intrahepatic inflammatory cells and mediators of islet destruction, including high‐mobility group box‐1, tissue factor, and IL‐1β. These findings support the use of CD47 as an innate immune checkpoint to mitigate IBMIR for enhanced islet engraftment with translational potential. Abstract : Pancreatic islets engineered to transiently display a novel form of CD47 modulate innate immune responses, resulting in enhanced engraftment and sustained survival in a mouse model of intraportal marginal mass islet transplantation.